KOMODIFIKASI AGAMA TERHADAP PEMBACAAN (KHATAMAN) ALQURAN AIR KEMASAN KH-Q PT. BUYA BAROKAH - Ahmad Nailul Fauzi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
This paper explains the commodification of religion in the form of the Qur'an recitation on Kh-Q bottled water in Kudus. Commodification is the process of transforming goods and services that once only have value-in-use (for example, the value-in-use of drinks is to quench the thirst, the value-in-use of stories is to communicate or share experiences) into commodities that have value-in-exchange because they can bring profits in the market (for example, after the drink is packed in bottles, after the story is written in a book or novel, or other examples, the commercialization of agriculture to sell food and drama production for commercial broadcasting). The phenomenon in Kudus reflects the existence of a commodity that blends with religion, which is the Qur’an recitation on the production of bottled water under the Kh-Q brand. This study used a descriptive-analytical approach as the analysis instrument for the recitation of Al-Qur`an (khataman) in Kudus. The results of the analysis in this study show that PT. Buya Barokah has placed religion, through recitation of the Qur'an (khataman), in one of its production processes. Kh-Q water, which is a product of PT. Buya Barokah, has had a dual role. Not only does this water circulate in the economy, but it also has a spiritual function as prayer water. The manifestation of religious commodification is found in the production of bottled water with the spirit of spiritual function of religion in Al-Qur'an recitation (khataman).